(untitled) - Danielson, Virginia (New York, 2002)
Expert writers present the major traditions of North Africa, the Middle East, and Central Asia, together with personal accounts of performers, composers, teachers, and ceremonies. A special feature of this volume is the inclusion of dozens of brief snap-shot essays that offer "lifestories" of typical musicmakers and their art, as well as first-person descriptions of specific music performances and events. Approximately 120 articles cover communities that preserve and enrich centuries-old traditions: "Music of the Jews of Djerba, Tunisia," "Following the Entranced Ones: Gnawa Performances and Trance in Rabat, Morocco," "Women's Music of the Arabian Peninsula," and "Vocal Music of Tuva." The volume explores such topics as political dissent, pop music genres, technology, poetry, gender, and the historical and scholarly roots of Middle Eastern music.
Keywords: Music,Folk music,Popular music; Encyclopedias,Encyclopedias,Encyclopedias